2007
DOI: 10.1029/2007gl032043
|View full text |Cite
|
Sign up to set email alerts
|

A younger, thinner Arctic ice cover: Increased potential for rapid, extensive sea‐ice loss

Abstract: [1] Satellite-derived estimates of sea-ice age and thickness are combined to produce a proxy ice thickness record for 1982 to the present. These data show that in addition to the well-documented loss of perennial ice cover as a whole, the amount of oldest and thickest ice within the remaining multiyear ice pack has declined significantly. The oldest ice types have essentially disappeared, and 58% of the multiyear ice now consists of relatively young 2-and 3-year-old ice compared to 35% in the mid-1980s. Ice co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
576
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 654 publications
(608 citation statements)
references
References 18 publications
30
576
0
2
Order By: Relevance
“…Similar to observations and hindcast simulations forced with atmospheric data (e.g. Maslanik et al 2007;Rothrock et al 2003), the simulated ice volume shows a considerable decline over the late twentieth to early twenty-first century in all of the CCSM3 standard runs with a corresponding reduction in the summer sea ice area. As discussed by Stroeve et al (2007), the reduction in September ice extent in these simulations is consistent with observed sea ice loss over the satellite record.…”
Section: Resultssupporting
confidence: 54%
“…Similar to observations and hindcast simulations forced with atmospheric data (e.g. Maslanik et al 2007;Rothrock et al 2003), the simulated ice volume shows a considerable decline over the late twentieth to early twenty-first century in all of the CCSM3 standard runs with a corresponding reduction in the summer sea ice area. As discussed by Stroeve et al (2007), the reduction in September ice extent in these simulations is consistent with observed sea ice loss over the satellite record.…”
Section: Resultssupporting
confidence: 54%
“…If the observed warming in the region of the Antarctic Peninsula (IPCC, 2007) results in a loss of multi-year ice in the western Weddell Sea, this may drive sympagic meiofauna communities into a state more similar to that in the southern Indian Ocean. In the Arctic Ocean, a reduction in sea-ice age has already been observed (Rigor and Wallace, 2004;Maslanik et al, 2007;Nghiem et al, 2007;Drobot et al, 2008), and the complete loss of multi-year ice has been predicted to occur before the middle of this century Wang and Overland, 2009). We assume that this development will result in a loss in diversity, abundance and biomass of sympagic meiofauna.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Phase III, the transmittance of FYI decreases to 0.04 and, for MYI, to 0.02 until FO. Additionally, sea ice that survives the summer melt is promoted to 1-year older ice in weeks 36-37 according to Maslanik et al (2007), and new ice forms. The transmittance of new first-year ice evolves correspondingly to the melting sea ice surface described above.…”
Section: Phase V: Fall Freeze-up (From Efo To Fo)mentioning
confidence: 99%
“…The evolution of Arctic sea ice towards a thinner, younger, and more seasonal sea ice cover during the last few decades (e.g., Comiso, 2012;Haas et al, 2008;Maslanik et al, 2007Maslanik et al, , 2011) has a strong impact on the partitioning of solar energy between the atmosphere, sea ice, and ocean (e.g., Perovich et al, 2007bPerovich et al, , 2011aWang et al, 2014). Decreased surface albedo (Perovich et al, 2011a), earlier melt onset, and a longer melt season (Markus et al, 2009, updated) have contributed to the observed increases in sea ice and snow melt (Perovich and Richter-Menge, 2009), and higher absorption and transmission of solar irradiance within and through Arctic sea ice Stroeve et al, 2014).…”
Section: Introductionmentioning
confidence: 99%